2018
DOI: 10.1002/jctb.5765
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol valorization to lactic acid catalyzed by hydroxyapatite‐supported palladium particles

Abstract: BACKGROUND Catalytic formation of lactic acid from biomass glycerol is a sustainable alternative to the conventional fermentation process starting from carbohydrate and the chemical route using HCN and acetaldehyde. Highly concentrated glycerol can be effectively converted to lactic acid using hydroxyapatite‐supported palladium particles in the presence of NaOH. RESULTS The 3% hydroxyapatite‐supported palladium catalyst (Pd3/HAP) demonstrates excellent activity (TOF = 1274 h−1 for a batch time of 90 min) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 56 publications
(232 reference statements)
1
32
0
Order By: Relevance
“…14 In addition, the fermentation route may not be able to meet the growing demand for LA of the chemical industry. 15 Research of new alternatives for chemical routes to produce LA has been of great interest in the last decades. 16 One of the alternative production routes is the hydrothermal conversion of glycerol to LA in alkaline medium which was rst described by Kishida et al 17 In this study Kishida used an autoclave reactor and NaOH or KOH as catalyst and aer 90 min at 300 C an aqueous solution of glycerol was converted into sodium lactate with yield higher than 90 mol% with 100% of glycerol conversion, employing NaOH or KOH/glycerol molar ratio equal to 3.78.…”
Section: Introductionmentioning
confidence: 99%
“…14 In addition, the fermentation route may not be able to meet the growing demand for LA of the chemical industry. 15 Research of new alternatives for chemical routes to produce LA has been of great interest in the last decades. 16 One of the alternative production routes is the hydrothermal conversion of glycerol to LA in alkaline medium which was rst described by Kishida et al 17 In this study Kishida used an autoclave reactor and NaOH or KOH as catalyst and aer 90 min at 300 C an aqueous solution of glycerol was converted into sodium lactate with yield higher than 90 mol% with 100% of glycerol conversion, employing NaOH or KOH/glycerol molar ratio equal to 3.78.…”
Section: Introductionmentioning
confidence: 99%
“…As the glycerol concentrations were increased from 1.5 to 3.0 mol L −1 , the glycerol conversions over CuPd 0.5 , CuPd 1 , CuPd 2 , CuPd 3 , CuPd 4 , and CuPd 5 catalysts decreased from 96.0% to 89.2%, 97.3% to 90.5%, 98.4% to 92.3%, 98.5% to 94.7%, 99.5% to 97.1%, and 100% to 96.9%, respectively, showing a decrease trend for the glycerol conversions. bimetallic CuPd x catalysts can provided abundant reactive sites for the glycerol molecules, leading to efficient conversion process in low glycerol concentration (Shen et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of NaOH has a positive effect on glycerol deprotonation, thus the conversion increases with the molar ratio of NaOH/glycerol. However, studies on glycerol alkaline hydrothermal conversion to lactic acid indicated that low concentration of NaOH are more effective for obtaining high glycerol conversion and lactic acid yields due to the relative solubility in water (Shen et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations